Kombinasi Edugame Dan Demonstrasi Balut Bidai Terhadap Kemampuan Pertolongan Pertama Korban Kecelakaan Lalu Lintas - Didit Damayanti; Dhina Widayati; Baghase Prasetyo (Universitas Muhamadiyah Manado, 2024)
The high number of traffic accidents in Indonesia is caused by heavy traffic, non-compliance with regulations, and inadequate infrastructure. Quick and appropriate first aid in traffic accidents is essential to increase the victim's chances of safety and survival. However, many lay people do not have the knowledge or skills to provide first aid. The aim of this research is to determine the effect of a combination of educational games and splint bandage demonstrations on the first aid abilities of traffic accident victims (Study at SMA N 1 Gurah, Kediri Regency). The research design used was a pre-experimental design with a one group pretest-posttest design. The sampling technique used proportionate random sampling to obtain 35 respondents. The research instrument used an observation sheet, data analysis using the Wilcoxon test. The results of the study showed that the majority (60%) before being given the edugame method and splint dressing demonstration had first aid abilities for accident victims in the poor category, while almost all (94.3%) after being given the edugame method and splint dressing demonstration had first aid abilities for accident victims in the good category. The Wilcoxon test result was 0.001, indicating that there was an influence of the combination of edugames and splint dressing demonstrations on the ability to provide first aid to traffic accident victims (p value = 0.001 <α = 0.05). Providing edugames can create fun learning and increase interest in learning and understanding that is easy to understand. Apart from that, the demonstration method also influences changes in the ability category because you can see directly and practice first aid how to apply splints. It is hoped that edugame and demonstration learning methods can be used as useful learning methods in modern education, increasing student involvement and making learning objectives easier for teenagers to understand.